Nutritional Risk Index Improves the GRACE Score Prediction of Clinical Outcomes in Patients With Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention - Ma, Xiao-Teng; Shao, Qiao-Yu; Li, Qiu-Xuan; Yang, Zhi-Qiang; Han, Kang-Ning; Liang, Jing; Shen, Hua; Liu, Xiao-Li; Zhou, Yu-Jie; Wang, Zhi-Jian (Frontiers in Cardiovascular Medicine, 2021)
Background: Malnutrition has been shown to be associated with adverse cardiovascular outcomes in many patient populations. Aims: To investigate the prognostic significance of malnutrition as defined by nutritional risk index (NRI) in patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) and whether NRI could improve the GRACE score based prognostic models. Methods: This study applied NRI among 1718 patients with ACS undergoing PCI. Patients were divided into 3 nutritional risk groups according to their baseline NRI: no nutritional risk (NRI ≥ 100), mild nutritional risk (97.5 ≤ NRI < 100), and moderate-to-severe nutritional risk (NRI < 97.5). The primary endpoint was the composite of major adverse cardiovascular events (MACE), including all-cause death, non-fatal stroke, non-fatal myocardial infarction, or unplanned repeat revascularization. Results: During a median follow-up of 927 days, 354 patients developed MACE. In the overall population, compared with normal nutritional status, malnutrition was associated with increased risk for MACE (adjusted HR for mild and moderate-to-severe nutritional risk, respectively: 1.368 [95%CI 1.004-1.871] and 1.473 [95%CI 1.064-2.041]), and NRI significantly improved the predictive ability of the GRACE score for MACE (cNRI: 0.070, P = 0.010; IDI: 0.005, P < 0.001). In the diabetes subgroup, malnutrition was associated with nearly 2-fold high adjusted risk of MACE, and the GRACE score combined with NRI appeared to have better predictive ability than that in the overall population. Conclusion: Malnutrition as defined by NRI was independently associated with MACE in ACS patients who underwent PCI, especially in individuals with diabetes, and improved the predictive ability of the GRACE score based prognostic models.